Anomalous Magnetism in Ferromagnetic Pyrochlores as Revealed By Neutron Scattering - Buhariwalla, Connor R. C. (My University, 2017)
This work is the result of two separate lines of study into the family of frustrated rare-earth pyrochlores with ferromagnetic interactions. The first is an examination of Yb2Ti2O7 and Ho2Ti2O7 through small angle neutron scattering (SANS) techniques. The sensitivity to anisotropic ferromagnetic correlations of SANS makes it an ideal tool to investigate the anomalous scattering of Yb2Ti2O7 , and to take a closer look into the low Q region of the spin ice Ho2Ti2O7 , where long range dipolar effects modify magnetic scattering. We show that in Yb2Ti2O7 the ferromagnetic order observed by other researchers coexists with short range HHH correlations to 0.03 K. We identify a new feature in Yb2Ti2O7 , a medium range (on the order of 100 ̊A) ferromagnetic correlation which appears to correlate well with the systems heat capacity anomaly. In Ho2Ti2O7 , we observe isotropic magnetic scattering in the low Q region that correlates to the system heat capacity anomaly. The second research project involves the system Ho2Sn2−xTixO7 with x=0,0.5,1,1.5,2. We use SQUID magnetometry and inelastic neutron scattering to examine the effects of B-site disorder on the spin ice system. We find some discrepancies with previous generation instrument results for the crystal electric field (CEF) Hamiltonian, and find results consistent with our previously hypothesized picture of the effects of B-site disorder on the CEF levels. We also observe increased spin dynamics in the disordered compounds, which is consistent with recent theory work predicting a transition to a quantum spin liquid phase in disordered non-kramers spin ice compounds.
Keywords: neutron; pyrochlore; frustrated magnetism; small angle scattering; inelastic scattering